Common sense economics : what everyone should know about wealth and prosperity - Gwartney, James D.; Lee, Dwight R.; Ferrarini, Tawni Hunt; Calhoun, Joseph P.; Shaw Stroup, Jane (St. Martin's Press, 2024)
The fully revised and updated fourth edition of the classic Common Sense Economics. As the global economy recovers from the COVID-19 pandemic and debates over the future of work challenge our long-held preconceptions about what careers and the market can be, learning the basics of economics has never been more essential. Principles such as gains from trade, the role of profit and loss, and the secondary effects of government spending, taxes, and borrowing risk continue to be critically important to the way America's economy functions, and critically important to understand for those hoping to further their professional lives - even their personal lives. Common Sense Economics discusses these key points and theories and more, using them to show how any reader can make wiser personal choices and form more informed positions on policy. Now in its fourth edition, this classic from James D. Gwartney, Jane S. Stroup, Dwight R. Lee, and Tawni H. Ferrarini has been fully updated to include commentary on the effects of the pandemic on the global economy and the workplace; it offers insight into political processes and the many ways in which economics informs policy, illuminating our world and what might be done to make it better